Preparation method of carbon fiber with cellulose as precursor

Through the carbon fiber preparation method with cellulose as the precursor, the complex and high cost of viscose-based carbon fiber production process is solved, and the high-performance carbon fiber preparation of cellulose fibers is achieved, with excellent mechanical, electrical and thermal conductivity.

CN119194668APending Publication Date: 2024-12-27CHINA PHARM UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411314712.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing viscose-based carbon fiber production process is complex, the production cost is high, and the performance is poor, resulting in the inability to further improve the performance.

Method used

Using a carbon fiber preparation method with cellulose as the precursor, including dissolving the cellulose derivative in an organic solvent, spinning to form fibers, and undergoing alkaline saponification treatment, drying, pre-oxidation and carbonization processes, and finally in an inert gas atmosphere The temperature was raised to 1200°C to produce carbon fiber.

Benefits of technology

Through the protection and removal of hydrogen bonds, the mechanical properties and molecular chain orientation of cellulose fibers are improved, and the carbon fibers prepared have excellent electrical conductivity, thermal conductivity, tensile strength, and flame retardant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194668A_ABST
    Figure CN119194668A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing carbon fibers by taking cellulose as a precursor. The preparation method comprises the following steps: dissolving cellulose ester (cellulose derivative) in a proper organic solvent, then extracting spinning fibers from the spinning solution on a large scale, and re-establishing hydrogen bonds among cellulose molecules by the obtained cellulose ester fibers through dederivatization (deesterification) so as to form the cellulose fibers. Cellulose fibers are fully soaked in the catalyst and then dried. And then pre-oxidizing and carbonizing the dried cellulose fiber to finally prepare the carbon fiber. The conductivity coefficient of the obtained carbon fiber is 230s cm <-1 >, the heat conductivity coefficient is 434.3 W m <-1 > K <-1 >, the tensile strength is 478 MPa, and the carbon fiber shows good conductivity and mechanical properties. Compared with the existing carbon fiber preparation technology, the invention provides a carbon fiber preparation strategy taking the novel cellulose fiber as the precursor, and the preparation method is simple, convenient, low in cost and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing carbon fiber, and in particular relates to a method for preparing carbon fiber using cellulose as a precursor. Background Art

[0002] At present, carbon fiber is mainly divided into three categories: polyacrylonitrile (PAN)-based carbon fiber, asphalt-based carbon fiber and viscose-based carbon fiber. Among them, PAN-based carbon fiber is the mainstream, and viscose-based carbon fiber accounts for less than 1%. my country is a major producer of cotton pulp, and its raw material advantage has laid a good foundation for the development of my country's viscose-based carbon fiber industry. However, the global high-end viscose-based carbon fiber market is mainly concentrated in Europe and the United States, and Chinese companies lack high-end competitive advantages.

[0003] Viscose-based carbon fiber has a wide range of applications in the fields of thermal insulation materials, aerospace, national defense and military industry, medical materials, etc. However, compared with PAN-based carbon fiber, viscose-based carbon fiber has complex technology, cumbersome production process, and high production cost; in addition, the performance of viscose-based carbon fiber precursor is poor, resulting in the inability to further improve the performance of viscose-based carbon fiber. Therefore, the key to improving the performance of viscose-based carbon fiber is to increase the molecular orientation in the precursor. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of complex production process, high production cost and poor performance of raw fibers in the existing preparation of viscose-based carbon fibers, and to propose a method for preparing carbon fibers using cellulose as a precursor.

[0005] A method for preparing carbon fiber using cellulose as a precursor, the preparation method comprising the following steps:

[0006] Step 1: dissolving the cellulose derivative in an organic solvent to form a uniform and transparent cellulose solution;

[0007] Step 2: Forming the obtained cellulose spinning solution into fibers using a specific spinning process;

[0008] Step 3: soaking the obtained derivatized cellulose fibers in an alkaline saponification solution under a certain stress to obtain cellulose fibers;

[0009] Step 4: Treat the cellulose fibers with a suitable impregnating agent, take them out and dry them;

[0010] Step 5: Pre-oxidation process, heating the fiber from room temperature to 300°C in air;

[0011] Step 6: Carbonization process: in an inert gas atmosphere, the temperature is raised to 1200°C and then cooled to obtain carbon fiber.

[0012] Furthermore, the cellulose derivatives in step 1 include: any cellulose ester or cellulose ester ether mixed derivative of cellulose formate, cellulose acetate, cellulose diacetate, cellulose triacetate, cellulose acetate, cellulose propionate, cellulose isopropionate, cellulose butyrate, cellulose acetate butyrate and cellulose xanthate, cellulose acetate propionate and cellulose acetate propionate.

[0013] Furthermore, the solvent for dissolving the cellulose derivative in step 1 includes: trifluoroacetic acid / dichloromethane or trifluoroacetic acid / water, wherein the volume ratio of trifluoroacetic acid to dichloromethane ranges from 1:0 to 2:3, and the volume ratio of trifluoroacetic acid to water ranges from 1:0 to 2:3.

[0014] Furthermore, the specific spinning method in step 1 includes drawing, dry spinning or dry-jet wet spinning.

[0015] Furthermore, the pulling spinning method is to insert the stainless steel rod into the cellulose solution to a depth of 0.2-1.5 mm and draw out the filaments at a speed of 0.1-1 cm / s, and the diameter of the obtained fiber can be controlled between 4.0 and 12.0 m;

[0016] The dry spinning method is to place the cellulose solution in a needle tube with an inner diameter of 0.16-0.33 mm, extrude at a speed of 5.1-15.5 m / s, and form filaments in an environment with an air humidity of 20% RH;

[0017] The dry-jet wet spinning method is to place the cellulose solution in a needle tube with an inner diameter of 0.16-0.33 mm, extrude it at a speed of 5.1-15.5 m / s, and after contacting with air for a period of time, put it into a coagulation bath with water as the medium to form fibers, take it out of the coagulation bath, and dry it to form filaments;

[0018] The cellulose solution is obtained by dissolving 15 wt % cellulose in trifluoroacetic acid / dichloromethane or trifluoroacetic acid / water at a ratio of V:V=3:2.

[0019] Furthermore, in step 3, stress-bearing cellulose triacetate fibers are immersed in an alkaline solution of sodium methoxide / methanol to remove acetyl groups to obtain cellulose fibers.

[0020] Furthermore, step 4 is to set the temperature in the oven to 50-60° C., and then place the soaked cellulose fibers in the oven for drying.

[0021] Furthermore, the impregnating agent in step 4 includes inorganic phosphate or nitrogen-containing sulfate of ammonium dihydrogen phosphate solution (5-10wt%) and diammonium hydrogen phosphate solution (5-10wt%), and the immersion time is 2-5 days. The impregnating agent has a flame retardant effect, can make the dehydration and pyrolysis reaction of the original fiber structure move to a low temperature, alleviate the thermal cracking and dehydration reaction, and inhibit the occurrence of the side reaction of producing levoglucose, so that the oxidative decomposition time can be extended, which helps to reduce the hole defects on the fiber surface and improve the performance of the carbon fiber.

[0022] Furthermore, in step 5, the pre-oxidation process is to heat the fiber in air from room temperature to 300°C at a heating rate of 1-10°C / min, and keep the temperature at 300°C for 0-5h;

[0023] Furthermore, in step 6, in the carbonization process, the temperature is increased at a rate of 1-10°C / min under a nitrogen atmosphere, maintained at 1200°C for 0-5h, and then naturally cooled to room temperature to obtain carbon fiber.

[0024] Furthermore, the inert gas described in the present invention is nitrogen or argon.

[0025] The advantages and beneficial effects of the present invention are:

[0026] 1. In the present invention, since the hydrogen bonds are protected by the derivatized functional groups, the molecular chain level dispersion in the spinning solution gives the derivatized cellulose fibers good mechanical properties.

[0027] 2. The present invention removes the derivatized functional groups of the derivatized cellulose fibers through an alkaline solution, and the hydrogen bonds are reconnected again. Because the molecular chains are well oriented, the molecular chain level is first dissolved and neatly arranged through the wrapping hydrogen bonds, and then the wrapping is removed and the hydrogen bonds are reconnected, resulting in a significant breakthrough in the mechanical properties of the prepared cellulose fibers.

[0028] 3. The cellulose triacetate prepared by the present invention is fully stretched during the spinning process, so that its molecular chain arrangement and orientation are good. Moreover, because the hydrogen bonds are protected by acetyl groups, the molecular chain level dispersion in the spinning solution gives the cellulose triacetate good mechanical properties, and it is a good precursor for carbon fibers.

[0029] 4. The carbon fiber of the present invention does not burn when encountering fire and has flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 To obtain a carbon fiber pattern;

[0031] Figure 2 This is the SEM image of the original silk fiber surface. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the embodiments.

[0033] The present invention provides a method for preparing carbon fiber using cellulose as a precursor, comprising the following steps:

[0034] Step 1: dissolving the cellulose derivative in an organic solvent to form a uniform and transparent solution;

[0035] Step 2: The spinning solution is formed into fibers using a specific spinning process;

[0036] Step 3: soaking the obtained derivatized cellulose fibers in an alkaline saponification solution under a certain stress to obtain cellulose fibers;

[0037] Step 4: Treat the cellulose fibers with a suitable impregnating agent, take them out and dry them;

[0038] Step 5: Pre-oxidation process, heating the fiber from room temperature to 300°C in air;

[0039] Step 6: Carbonization process: in a nitrogen atmosphere, the temperature is raised to 1200°C, and then cooled to obtain carbon fiber.

[0040] The obtained carbon fiber Figure 1 shown.

[0041] Embodiment 1:

[0042] After the trifluoroacetic acid solution and the dichloromethane solution with a volume ratio of 3:2 are mixed evenly, the cellulose triacetate is added to the mixed solution and stirred for 6 hours until it is completely dissolved and becomes a transparent cellulose triacetate solution. The spinning solution is slowly extracted with a syringe and the syringe is placed vertically. A six-hole needle is installed on the syringe, and appropriate pressure is applied to the syringe to make the spinning solution flow out evenly. The spinning solution is collected with a drum collector. During the collection process, the solvent evaporates immediately and is dried at a relative humidity (RH) of 20% to obtain cellulose triacetate fiber. The obtained cellulose triacetate fiber is folded in half and hung with appropriate weights, soaked in an alkaline solution (sodium methoxide / methanol), and stress is applied to the fiber by hanging weights to remove acetyl groups, thereby obtaining cellulose fiber. After saponification, the cellulose fiber is thoroughly rinsed with deionized water and air-dried at room temperature for 12 hours. The dried fiber is heated from room temperature to 300°C in air at a heating rate of 5°C / min, then heated to 1000°C in a nitrogen atmosphere at a heating rate of 5°C / min, maintained for 2 hours, and then cooled to obtain carbon fiber.

[0043] The carbon fiber finally obtained in this embodiment was subjected to the following tests:

[0044] Conductivity test: Conduct conductivity test on carbon fiber. The conductivity coefficient of carbon fiber is 230s cm -1 , showing excellent electrical conductivity;

[0045] Thermal conductivity test: thermal conductivity test of carbon fiber. The thermal conductivity coefficient of carbon fiber is 434.3W m -1 K -1 .

[0046] Mechanical strength test: The mechanical properties of carbon fiber are tested. The tensile strength of carbon fiber is 478MPa.

[0047] Embodiment 2:

[0048] After the trifluoroacetic acid solution and the dichloromethane solution with a volume ratio of 3:2 are mixed evenly, the cellulose triacetate is added to the mixed solution and stirred for 6 hours until it is completely dissolved and becomes a transparent cellulose triacetate solution. The spinning solution is slowly extracted with a syringe and the syringe is placed vertically. A six-hole needle is installed on the syringe, and appropriate pressure is applied to the syringe to make the spinning solution flow out evenly. The spinning solution is collected with a drum collector. During the collection process, the solvent evaporates immediately and is dried at a relative humidity (RH) of 20% to obtain cellulose triacetate fiber. The obtained cellulose triacetate fiber is folded in half and hung with appropriate weights, immersed in an alkaline solution (sodium methoxide / methanol), and stress is applied to the fiber by hanging weights to remove acetyl groups, thereby obtaining cellulose fiber. After saponification, the cellulose fiber is thoroughly rinsed with deionized water and air-dried at room temperature for 12 hours. The dried fiber is heated from room temperature to 300°C in air at a heating rate of 5°C / min, then heated to 1200°C in a nitrogen atmosphere at a heating rate of 5°C / min, maintained for 2 hours, and then cooled to obtain carbon fiber.

[0049] The carbon fiber finally obtained in this embodiment was subjected to the following tests:

[0050] Conductivity test: Conductivity test of cellulose triacetate fiber. The conductivity coefficient of carbon fiber is 215scm -1 , showing excellent electrical conductivity;

[0051] Thermal conductivity test, thermal conductivity test of cellulose triacetate fiber. The thermal conductivity coefficient of carbon fiber is 408.5Wm -1 K -1 .

[0052] Mechanical strength test: The mechanical properties of carbon fiber are tested. The tensile strength of carbon fiber is 452MPa.

[0053] Embodiment 3:

[0054] After the trifluoroacetic acid solution and the dichloromethane solution with a volume ratio of 3:2 are mixed evenly, the cellulose triacetate is added to the mixed solution and stirred for 6 hours until it is completely dissolved and becomes a transparent cellulose triacetate solution. The spinning solution is slowly extracted with a syringe and the syringe is placed vertically. A six-hole needle is installed on the syringe, and appropriate pressure is applied to the syringe to make the spinning solution flow out evenly. The spinning solution is collected with a drum collector. During the collection process, the solvent evaporates immediately and is dried at a relative humidity (RH) of 20% to obtain cellulose triacetate fiber. The obtained cellulose triacetate fiber is folded in half and hung with appropriate weights, soaked in an alkaline solution (sodium methoxide / methanol), and stress is applied to the fiber by hanging weights to remove acetyl groups, thereby obtaining cellulose fiber. After saponification, the cellulose fiber is thoroughly rinsed with deionized water and air-dried at room temperature for 12 hours. The dried fiber is heated from room temperature to 300°C in air at a heating rate of 5°C / min, then heated to 1400°C in a nitrogen atmosphere at a heating rate of 5°C / min, maintained for 2 hours, and then cooled to obtain carbon fiber.

[0055] The carbon fiber finally obtained in this embodiment was subjected to the following tests:

[0056] Conductivity test: Conductivity test of cellulose triacetate fiber. The conductivity coefficient of carbon fiber is 196scm -1 , showing excellent electrical conductivity;

[0057] Thermal conductivity test, thermal conductivity test of cellulose triacetate fiber. The thermal conductivity coefficient of carbon fiber is 352.4Wm -1 K -1 .

[0058] Mechanical strength test: The mechanical properties of carbon fiber are tested. The tensile strength of carbon fiber is 437MPa.

[0059] Embodiment 4:

[0060] After the trifluoroacetic acid solution and the dichloromethane solution with a volume ratio of 3:2 are mixed evenly, the cellulose triacetate is added to the mixed solution and stirred for 6 hours until it is completely dissolved and becomes a transparent cellulose triacetate solution. The spinning is carried out by the traction drawing method, and the spinning solution is collected by a drum collector. During the collection process, the solvent is immediately volatilized, and the cellulose triacetate fiber is dried at a relative humidity (RH) of 20% to obtain the cellulose triacetate fiber. The obtained cellulose triacetate fiber is folded in half and hung with appropriate weights, and soaked in an alkaline solution (sodium methoxide / methanol). The acetyl group is removed by applying stress to the fiber by hanging weight, thereby obtaining cellulose fiber. After saponification, the cellulose fiber is thoroughly rinsed with deionized water and air-dried at room temperature for 12 hours. The dried fiber is heated from room temperature to 300°C in air at a heating rate of 5°C / min, then heated to 1000°C in a nitrogen atmosphere at a heating rate of 5°C / min, maintained for 2 hours, and then cooled to obtain carbon fiber.

[0061] The carbon fiber finally obtained in this embodiment was subjected to the following tests:

[0062] Conductivity test: Conduct conductivity test on carbon fiber. The conductivity coefficient of carbon fiber is 229s cm -1 , showing excellent electrical conductivity;

[0063] Thermal conductivity test: thermal conductivity test of carbon fiber. The thermal conductivity coefficient of carbon fiber is 431.3W m -1 K -1 .

[0064] Mechanical strength test: The mechanical properties of carbon fiber are tested. The tensile strength of carbon fiber is 473MPa.

[0065] Embodiment 5:

[0066] After the trifluoroacetic acid solution and the dichloromethane solution with a volume ratio of 3:2 are mixed evenly, the cellulose triacetate is added to the mixed solution and stirred for 6 hours until it is completely dissolved and becomes a transparent cellulose triacetate solution. The spinning is carried out by the traction drawing method, and the spinning solution is collected by a drum collector. During the collection process, the solvent is immediately volatilized, and the cellulose triacetate fiber is dried at a relative humidity (RH) of 20% to obtain the cellulose triacetate fiber. The obtained cellulose triacetate fiber is folded in half and hung with appropriate weights, and soaked in an alkaline solution (sodium methoxide / methanol). The acetyl group is removed by applying stress to the fiber by hanging weight, thereby obtaining cellulose fiber. After saponification, the cellulose fiber is thoroughly rinsed with deionized water and air-dried at room temperature for 12 hours. The dried fiber is heated from room temperature to 300°C in air at a heating rate of 5°C / min, then heated to 1200°C in a nitrogen atmosphere at a heating rate of 5°C / min, maintained for 2 hours, and then cooled to obtain carbon fiber.

[0067] The carbon fiber finally obtained in this embodiment was subjected to the following tests:

[0068] Conductivity test: Conduct conductivity test on carbon fiber. The conductivity coefficient of carbon fiber is 208s cm -1 , showing excellent electrical conductivity;

[0069] Thermal conductivity test: thermal conductivity test of carbon fiber. The thermal conductivity coefficient of carbon fiber is 412.3W m -1 K -1 .

[0070] Mechanical strength test: The mechanical properties of carbon fiber are tested. The tensile strength of carbon fiber is 428MPa.

[0071] Embodiment 6:

[0072] After the trifluoroacetic acid solution and the dichloromethane solution with a volume ratio of 3:2 are mixed evenly, the cellulose triacetate is added to the mixed solution and stirred for 6 hours until it is completely dissolved and becomes a transparent cellulose triacetate solution. The spinning is carried out by the traction drawing method, and the spinning solution is collected by a drum collector. During the collection process, the solvent is immediately volatilized, and the cellulose triacetate fiber is dried at a relative humidity (RH) of 20% to obtain the cellulose triacetate fiber. The obtained cellulose triacetate fiber is folded in half and hung with appropriate weights, and soaked in an alkaline solution (sodium methoxide / methanol). The acetyl group is removed by applying stress to the fiber by hanging weight, thereby obtaining cellulose fiber. After saponification, the cellulose fiber is thoroughly rinsed with deionized water and air-dried at room temperature for 12 hours. The dried fiber is heated from room temperature to 300°C in air at a heating rate of 5°C / min, then heated to 1400°C in a nitrogen atmosphere at a heating rate of 5°C / min, maintained for 2 hours, and then cooled to obtain carbon fiber.

[0073] The carbon fiber finally obtained in this embodiment was subjected to the following tests:

[0074] Conductivity test: Conduct conductivity test on carbon fiber. The conductivity coefficient of carbon fiber is 201s cm -1 , showing excellent electrical conductivity;

[0075] Thermal conductivity test: thermal conductivity test of carbon fiber. The thermal conductivity coefficient of carbon fiber is 386.6W m -1 K -1 .

[0076] Mechanical strength test: The mechanical properties of carbon fiber are tested. The tensile strength of carbon fiber is 446MPa.

[0077] The carbon fiber prepared by the present invention with cellulose as the precursor has good conductivity and tensile strength, and the cellulose fiber precursor has a high degree of orientation (such as Figure 2 ), which provides the possibility for the good performance of carbon fiber.

Claims

1. A method for preparing carbon fiber using cellulose as a precursor, characterized in that: The preparation method comprises the following steps: Step 1: dissolving the cellulose derivative in an organic solvent to form a uniform and transparent cellulose solution; Step 2: The obtained cellulose solution spinning solution is formed into fibers by a specific spinning process; Step 3: soaking the obtained derivatized cellulose fibers in an alkaline saponification solution under a certain stress to obtain cellulose fibers; Step 4: Treat the cellulose fibers with a suitable impregnating agent, take them out and dry them; Step 5: Pre-oxidation process, heating the fiber from room temperature to 300°C in air; Step 6: Carbonization process: in an inert gas atmosphere, the temperature is raised to 1200°C and then cooled to obtain carbon fiber.

2. The preparation method according to claim 1, characterized in that: The cellulose derivatives in step 1 include: any cellulose ester or cellulose ester ether mixed derivative of cellulose formate, cellulose acetate, cellulose diacetate, cellulose triacetate, cellulose acetate, cellulose propionate, cellulose isopropionate, cellulose butyrate, cellulose acetate butyrate and cellulose xanthate, cellulose acetate propionate and cellulose acetate propionate.

3. The preparation method according to claim 1, characterized in that: The solvent for dissolving the cellulose derivative in step 1 includes: trifluoroacetic acid / dichloromethane or trifluoroacetic acid / water, wherein the volume ratio of trifluoroacetic acid to dichloromethane ranges from 1:0 to 2:3, and the volume ratio of trifluoroacetic acid to water ranges from 1:0 to 2:

3.

4. The preparation method according to claim 1, characterized in that: The specific spinning method in step 2 includes drawing, dry spinning or dry-jet wet spinning; The traction spinning method is to insert a stainless steel rod into a cellulose solution to a depth of 0.2-1.5 mm and draw out the filaments at a speed of 0.1-1 cm / s, and the diameter of the obtained fiber can be controlled between 4.0 and 12.0 μm; The dry spinning method is to place the cellulose solution in a needle tube with an inner diameter of 0.16-0.33 mm, extrude at a speed of 5.1-15.5 m / s, and form filaments in an environment with an air humidity of 20% RH; The dry-jet wet spinning method is to place the cellulose solution in a needle tube with an inner diameter of 0.16-0.33 mm, extrude it at a speed of 5.1-15.5 m / s, and after contacting with air for a period of time, put it into a coagulation bath with water as the medium to form fibers, take it out of the coagulation bath, and dry it to form filaments; The cellulose solution is obtained by dissolving 15 wt % cellulose in trifluoroacetic acid / dichloromethane or trifluoroacetic acid / water at a ratio of V:V=3:

2.

5. The preparation method according to claim 1, characterized in that: In step 3, stress-bearing cellulose fibers are applied and immersed in an alkaline solution of sodium methoxide / methanol to remove acetyl groups to obtain cellulose fibers.

6. The preparation method according to claim 1, characterized in that: Step 4 is to set the temperature in the oven to 50-60° C., and then place the soaked cellulose fibers in the oven for drying.

7. The preparation method according to claim 1, characterized in that: The impregnating agent in step 4 includes 5-10 wt % diammonium phosphate solution or 5-10 wt % diammonium hydrogen phosphate solution of inorganic phosphate or nitrogen-containing sulfate, and the soaking time is 2-5 days.

8. The preparation method according to claim 1, characterized in that: In step 5, the pre-oxidation process is to heat the fiber from room temperature to 300°C in air at a heating rate of 1-10°C / min, and keep it at 300°C for 0-5h.

9. The preparation method according to claim 1, characterized in that: In step 6, the carbonization process is carried out under an inert gas atmosphere at a heating rate of 1-10°C / min, maintaining at 1200°C for 0-5h, and naturally cooling to room temperature to obtain carbon fiber.

10. The preparation method according to claim 1 or 9, characterized in that: The inert gas is nitrogen or argon.

Citation Information

Cited By

  • Bio-based precursor suitable for producing high-modulus carbon fibers

    CN120042059A